The stage‐specific in vitro efficacy of a malaria antigen cocktail provides valuable insights into the development of effective multi‐stage vaccines. Issue 10 (26th May 2015) - Spiegel, Holger; Boes, Alexander; Kastilan, Robin; Kapelski, Stephanie; Edgue, Güven; Beiss, Veronique; Chubodova, Ivana; Scheuermayer, Matthias; Pradel, Gabriele; Schillberg, Stefan; Reimann, Andreas; Fischer, Rainer
Abstract Multicomponent vaccines targeting different stages of Plasmodium falciparum represent a promising, holistic concept towards better malaria vaccines. Additionally, an effective vaccine candidate should demonstrate cross‐strain specificity because many antigens are polymorphic, which can reduce vaccine efficacy. A cocktail of recombinant fusion proteins (VAMAX‐Mix) featuring three diversity‐covering variants of the blood‐stage antigen PfAMA1, each combined with the conserved sexual‐stage antigen Pfs25 and one of the pre‐erythrocytic‐stage antigens PfCSP_TSR or PfCelTOS, or the additional blood‐stage antigen PfMSP1_19, was produced in Pichia pastoris and used to immunize rabbits. The immune sera and purified IgG were used to perform various assays determining antigen specific titers and in vitro efficacy against different parasite stages and strains. In functional in vitro assays we observed robust inhibition of blood‐stage (up to 90%), and sexual‐stage parasites (up to 100%) and biased inhibition of pre‐erythrocytic parasites (0–40%). Cross‐strain blood‐stage efficacy was observed in erythrocyte invasion assays using four different P. falciparum strains. The quantification of antigen‐specific IgGs allowed the determination of specific IC50 values. The significant difference in antigen‐specific IC50 requirements, the direct correlation between antigen‐specific IgG and the relative quantitative representation of antigens within the cocktail, provide valuable implementations for future multi‐stage, multi‐component vaccine designs.